Dupilumab – a novel treatment option against allergic diseases: a state-of-the-art review - Kołakowska, Klaudia; Czubek, Maciej (Alergologia Polska - Polish Journal of Allergology, 2025)
Dupilumab is a humanized, IgG4 monoclonal antibody which binds to the α subunit of interleukin 4 receptor (IL-4R) and interleukin 13 receptor (IL-13R), thereby it inhibits their action. Interleukin 4 and interleukin 13 play a prominent role in the pathogenesis of allergic diseases. Dupilumab is registered for the treatment of asthma, moderate-to-severe atopic dermatitis and chronic rhinosinusitis with nasal polyps and eosinophilic esophagitis. The aim of this review is to present the current state of knowledge about the therapeutic indications of dupilumab and associated therapeutic consequences. Recent clinical trials have proven that dupilumab reduces the severity of atopic dermatitis symptoms and pruritus. Dupilumab improved the hydrolipid skin barrier in patients with atopic dermatitis. Dupilumab decreased the expression of genes associated with T cells, dendritic cells and chemokines involved in T2 immune response in patients with atopic dermatitis. Moreover, this antibody reduced the rate of annualized severe exacerbations in patients with asthma. Dupilumab decreased the level of type 2 inflammation biomarkers including nitric oxide in exhaled air, serum IgE, eotaxin-3, periostin in patients with asthma. Clinical trials conducted on patients with eosinophilic esophagitis showed that dupilumab reduced inflammation by lowering eosinophil count in the esophageal epithelium. Recent studies showed that dupilumab can be potentially used in other indications such as chronic dermatological diseases, respiratory diseases and gastrointestinal diseases. Despite the good safety profile of dupilumab, therapy with this drug is associated with numerous side effects including conjunctivitis, psoriasis, facial and neck erythema, arthritis, alopecia, injection site reaction and transient increases in eosinophil counts.